Feature Detection in Visual Cortex during Different Functional States - Esir, Pavel; Simonov, Alexander; Tsodyks, Misha (Frontiers in Computational Neuroscience, 2017)
Cortical activity exhibits distinct characteristics in different functional states. In awake behaving animals it shows less synchrony, while in rest or sleeping state cortical activity is most synchronous. Previous studies showed that switching between functional states can change the efficiency of flowing sensory information. Switching between functional states can be triggered by releasing neuromodulators which affect neurotransmitter release probability and depolarization of cortical neurons. In this work we focus on studying primary visual area V1, by using firing rate ring model with short-term synaptic depression (STD). We show that detection of visual inputs depends on the functional state, with best detection precision achieved at the state with intermediate release probability. We suggest that this regime corresponds to the state of maximal visual attention.